Masjid Sebagai Sentra Dakwah Wasathiyah (Studi Tentang Aktivitas Dakwah Masjid Agung Nurul Falah Kabupaten Paser) - Amirullah, Amirullah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This study is motivated by the mosque, which is considered "the House of Allah" and serves as an open space for everyone, particularly for the activities of wasathiyah (moderate) Islamic da’wa, presenting Islam's grand vision as a religion of rahmatan lil alamien (blessings for all creation). The importance of the mosque as a center for wasathiyah da’wa must be continuously maintained and preserved. The mosque acts as a neutral space that reflects the "face" of Islam, shaping the religiosity of Muslims. This research aims to present the Masjid Agung Nurul Falah in Paser Regency as a material object and a phenomenon of its role as a center of wasathiyah da’wa. This study employs a qualitative descriptive approach, with data collection through interviews, observations, and documentation. The findings indicate that the Islamic preaching activities at Masjid Agung Nurul Falah (MAN) are centered around wasathiyah Islam. The preaching at MAN adheres to strengthening the aqidah (creed) of Ahlus Sunnah. The construction of wasathiyah Islamic da’wa at MAN emphasizes four characteristics of wasathiyah Islam: tawassuth (taking the middle path), tawazun (balance), i’tidal (steadfast and upright), and tasamuh (tolerance). This approach represents the essence of Islam as rahmatan lil alamien, consistently positioned between extreme right (radicalism) and extreme left (liberalism) understandings.